Um estudo sobre a mobilidade ativa de idosos em uma cidade de porte médio a partir da abordagem socioecológica - Bernal, Luciana Mação (Universidade Federal de São Carlos, 2022)
The elderly population is increasing in Brazil and worldwide, highlighting the need for cities to prepare to welcome this population, guaranteeing them the quality of their mobility in a safe and autonomously way. This research aims to study the active mobility of the elderly in a medium-sized city based on a socioecological approach. This approach suggests verifying multiple levels of influence in the individual's relationship with the environment they are living in. For this study, four levels of influence were selected: individual, social, physical environment, and public policies. In other words, this study aims to identify factors that influence the active mobility of the elderly and to assess the perception of these individuals regarding each one of these factors. Furthermore, the study aims to analyze the importance of socioecological levels in the active mobility of the elderly. To achieve this, the most cited factors in the literature were selected and classified according to their respective socioecological level. After this stage, a questionnaire was developed and later applied in the city of São Carlos – SP, to assess the perception of the elderly to these selected factors. As a result, it was observed that at the individual level most of the elderly showed a positive attitude towards walking, demonstrating affinity with the practice. However, effectively, most of the elderly were classified as non-active individuals (walking less than 150 minutes a week). The social level indicated, in general, that support received from family and friends is neutral to encourage walking. Considering each factor in the social levels individually, family tends to encourage the elderly to walk more than encouragement from friends. The level of the physical environment of the neighborhood was also evaluated as neutral. Although factors such as the quality of sidewalks, aesthetics (eg. no weeds, garbage, etc.), and safety (eg. fear of being robbed or assaulted) were evaluated as bad, discouraging walking, factors such as mixed land-use and alternative paths acted as practice motivators. Regarding the political level, the elderly believe that public administration does not adequately maintain sidewalks and public spaces planned for pedestrians. Lastly, after evaluating the perception of the respondents, the binary logistic regression model was calibrated to verify which levels were most relevant for the elderly to be active, and from their results, a sensitivity analysis was performed to graphically represent the results obtained. It was observed that the most relevant level was the physical environment, followed by the individual level (represented by attitude) and social support level. The political level was not statistically significant in the regression model. In conclusion, understanding influence levels and verifying their importance is a starting point that allows city managers to plan their cities with a macro view. They can initially focus where intervention is most needed and, considering the elderly perception about factors corresponding to each level, it is possible to individually verify which one’s act as a barrier or stimulus, fostering information that makes it possible to create measures to encourage the active mobility of the elderly.
A study on the active mobility of the elderly in a medium-sized city through the socioecological approach
Keywords: Idosos; Mobilidade ativa; Caminhada; Modelo socioecológico; Elderly; Active mobility; Walking; Socioecological model; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES; ENGENHARIAS